STRATEGIES OF THE UNIVERSITIES IN MANAGING THE INTELLECTUAL CAPITAL WITHIN THE SMART CITY CONCEPT: NARRATIVE LITERATURE REVIEW - D. Zagulova (Real Economics Publishing House, 2021)
Smart City is the basic concept of urban development; it is based on technological solutions and intellectual capital. The universities are the principal structures developing the intellectual capital in the modern society. They often have the necessary technologies, but there is a significant gap between the existing solutions at the universities and their implementation in smart city. The origin of this problem is in the improper procedure of transferring these solutions from university to the city, business, state. The goal of this research is to present the existing possibilities of the universities in creating, developing, transferring and implementing the intellectual capital for the development of smart city. There presented the models of intellectual capital, intellectual capital is considered as an intellectual asset and its management is considered in accordance with the different types of the university. This procedure becomes possible due to the proper narrative literature review. Therefore, the described methodology of the literature review, integrating the various options of writing the systematic and the narrative reviews, is of special value.